Verification of Video Source Camera Competition (CAMCOM 2010) - van Houten, Wiger; Geradts, Zeno; Franke, Katrin; Veenman, Cor (Recognizing Patterns in Signals, Speech, Images and Videos, 2010)
Digital cameras are being integrated in a large number of mobile devices. These devices may be used to record illegal activities, or the recordings themselves may be illegal. Due to the tight integration of these mobile devices with the internet, these recordings may quickly find their way to internet video-sharing sites such as YouTube. In criminal casework it is advantageous to reliably establish the source of the video. Although this was shown to be doable for relatively high quality video, it is unknown how these systems perform for low quality transcoded videos. The CAMCOM2010 contest is organized to create a benchmark for source video identification, where the videos originate from YouTube. Despite the number of participants was satisfactory initially, only two participants submitted results, mostly due to a lack of time. Judging by the performance of the contestants, this is certainly not a trivial problem.